Association between Allium vegetables and the risk of non-digestive tract cancer: A systematic review and meta-analysis of cohort and case-control studies. (2022) - Guo, Lei; Yuan, Xiaofan; Yang, Bo; Tang, Guo; Liang, Hanbai; Guo, Fuqiang
Highlights: Previous studies yield conflicting results about the effect of allium vegetables on cancer risk. The effect of allium vegetable on non-digestive tract cancer risk was firstly evaluated using a meta-analysis method. Allium vegetables decreased the risk of non-digestive tract cancer. Curvilinear association existed between allium vegetable consumption and non-digestive tract cancer risk. Abstract: Purpose: To clarify the role of Allium vegetables in non-digestive tract cancer, we conducted this meta-analysis. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we conducted a meta-analysis of published studies assessing the associations between Allium vegetables and the risk of non-digestive tract cancer. We estimated the pooled odds ratio (OR) of non-digestive tract cancer for the highest and lowest Allium vegetable consumption using random-effects models. A dose-response regression model was used to evaluate the relationship between Allium vegetables and non-digestive tract cancer risk. Results: In a pooled analysis of 25 studies (11 cohort and 14 case-control studies) on Allium vegetables, a total of 18, 070 patients with non-digestive tract cancer were finally included. Integrated OR of non-digestive tract cancer was 0.86 [95% confidence interval (CI):0.80–0.93] for the highest versus the lowest Allium vegetable consumption for all studies, 0.78 (95% CI:0.69–0.90) for case-control studies and 0.94 (95%CI: 0.87–1.02) for cohort studies. Sensitivity analysis showed that the pooled effect was stable. No apparent publication bias was identified in this study; however, the cumulative meta-analysis suggested that studies conducted earlier (from 1994 to 1997) might be a source of heterogeneity. Dose-response regression model indicated that Allium vegetable consumption was associated with the risk of non-digestive tract cancer ( P  = 0.001 for non-linearity; P  = 0.032 for linearity). Conclusion: Higher Allium vegetable consumption could reduce the risk of non-digestive tract cancers, demonstrating the protective role of Allium vegetables.